Different concentrations of progesterone in follicular fluid modulates molecular patterns of follicular environment components - Rosa, Paola Maria da Silva (2024)
During folliculogenesis, ovarian follicle compartments can interact via small extracellular vesicles (sEVs) secreted into follicular fluid (FF), facilitating communication among follicular components and contributing to oocyte competence. However, fluctuations in FF composition during the estrous cycle can modulate the metabolism, molecular responses of follicular cells, and sEV content. Progesterone (P4) plays a pivotal role in regulating the ovulatory cycle, follicular development, and oogenesis. Several studies have hinted at a correlation between P4 levels and oocyte quality. Hence, selecting an optimal follicular environment with appropriate P4 levels may enhance oocyte competence and in vitro embryo production rates. The hypothesis of this study posits that varying concentrations of P4 in ovarian follicles with diameters of 3-6mm differently influence the follicular environment components. This hypothesis was tested through two experiments: firstly, characterizing the environment of 3-6mm follicles with different P4 concentrations in ovaries ipsilateral and contralateral to the corpus luteum, and secondly, characterizing follicular components exposed to varied P4 concentrations in 3-6mm follicles aspirated from ipsilateral and contralateral ovaries of synchronized Nellore cows, along with the impact of different P4 supplementation levels during in vitro maturation (IVM) on oocyte communication and maturation. Results from the first study showed that varying P4 concentrations in follicular fluid did not affect the rate of viable oocyte recovery. However, a high P4 environment increased the expression of genes associated with oocyte maturation (ADAMTS-1) and miRNA biosynthesis (AGO2) in cumulus and granulosa cells, respectively. Additionally, high P4 follicular fluid exhibited distinct miRNA profiles, indicative of varied biological pathways compared to the low P4 group.In the second study, EV proteins from high P4 follicular fluid were found to regulate biological pathways linked to the ERK1/ERK2 regulatory cascade. Moreover, cumulus cells from the low P4 environment were observed to regulate cellular components related to cellular communication. Finally, supplementation with high and low doses of P4 during IVM suggested that high P4 induces a retraction of transzonal projections (TZPs). Collectively, these findings suggest that a high P4 environment in follicles may prematurely trigger certain oocyte maturation processes, potentially compromising oocyte competence. Nevertheless, further studies are warranted to validate the effects of P4 during IVM on oocyte competence and embryonic development.